Exploration of Batak Culture as Sources of Learning Batak Toba Dance - Yusnizar Heniwaty; Sitti Rahmah (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2022)
This study describes cultural exploration that is used as a source of learning, this is related to how to introduce culture which can be done through art learning in formal activities and informal activities. Through the exploration of traditional culture, in this case the art of dance, efforts to preserve, introduce, inherit, and develop traditional arts become part of strengthening attitudes in understanding norms, values in society. "Tortor" as one of the traditional arts of the Batak tribe becomes one of the subjects of learning in formal activities and becomes a must-have competency, also in informal activities. In the learning process, knowledge is not only given in text (dance form), but the context of the dance is a part that must be introduced as local content. This is done as a strengthening of the knowledge of graduates as prospective teachers, who function as motivators, facilitators, and how to present them in class so that PBM can be successful. However, in the learning process there are still many obstacles, especially the lack of learning resources related to the cultural context of the community, as a basis for understanding in learning traditional dance. Especially with technological advances that require lecturers to be more creative in the process of transferring knowledge. Based on this, the aim of this research is to focus on exploring Batak culture in relation to the preservation of traditional arts as a learning resource. The research was conducted by observation, interview, and recording.